Geochronology and Geochemistry of Early Cretaceous Granitic Plutons in the Xing'an Massif, Great Xing'an Range, NE China: Petrogenesis and Tectonic Implications. (29th October 2019) - DONG, Yu; GE, Wenchun; TIAN, Dexin; JI, Zheng; YANG, Hao; BI, Junhui; WU, Haoran; HAO, Yujie
Abstract : Abstract : In this study, we present zircon U‐Pb ages, whole‐rock geochemical data and Hf isotopic compositions for the Meiguifeng and Arxan plutons in Xing'an Massif, Great Xing'an Range, which can provide important information in deciphering both Mesozoic magmatism and tectonic evolution of NE China. The zircon U‐Pb dating results indicate that alkali feldspar granite from Meiguifeng pluton was emplaced at ∼145 to 137 Ma, and granite porphyry of Arxan pluton was formed at ∼129 Ma. The Meiguifeng and Arxan plutons have similar geochemical features, which are characterized by high silica, total alkalis, differentiation index, with low P2 O5, CaO, MgO, TFe2 O3 contents. They belong to high‐K calc‐alkaline series, and show weakly peraluminous characteristics. The Meiguifeng and Arxan plutons are both enriched in LREEs and LILEs (e.g., Rb, Th, U and K), and depleted in HREEs and HFSEs (e.g., Nb, Ta and Ti). Combined with the petrological and geochemical features, the Meiguifeng and Arxan plutons show highly fractionated I‐type granite affinity. Moreover, the Meiguifeng and Arxan plutons may share a common or similar magma source, and they were probably generated by partial melting of Neoproterozoic high‐K basaltic crust. Meanwhile, plagioclase, K‐feldspar, biotite, apatite, monazite, allanite and Ti‐bearing phases fractionated from the magma during formation of Meiguifeng and Arxan plutons. Combined with spatial distribution and temporal evolution, we assume that the generation of Early Cretaceous Meiguifeng and Arxan plutons in Great Xing'an Range was closely related to the break‐off of Mudanjiang oceanic plate. Furthermore, the Mudanjiang Ocean was probably a branch of Paleo‐Pacific Ocean.